An open, prospective cohort study of VV116 in Chinese participants infected with SARS-CoV-2 omicron variants. Issue 1 (31st December 2022) - Shen, Yinzhong; Ai, Jingwen; Lin, Na; Zhang, Haocheng; Li, Yang; Wang, Hongyu; Wang, Sen; Wang, Zhen; Li, Tao; Sun, Feng; Fan, Zhenyu; Li, Liqun; et al.
ABSTRACT: Omicron variant of SARS-CoV-2 has become the predominant variant worldwide. VV116 is an oral drug with robust anti-SARS-CoV-2 efficacy in preclinical studies. We conducted an open, prospective cohort study to evaluate its safety and effectiveness in Chinese participants infected with the omicron variant from March 8th, 2022 to March 24th, 2022. 136 hospitalized nonsevere patients confirmed with COVID-19 were enrolled including 60 patients who received VV116 (300 mg, BID×5 days) in the treatment group and 76 patients who didn't receive VV116 in the control group besides standard treatment. Viral load shedding time and adverse events were collected during the follow-up. There was no significant difference in baseline characteristics between the VV116 group and the control group, except for a higher symptom prevalence in the control group ( P = 0.021). The median time from the first positive test to the first VV116 administration was 5 (range: 2-10) days. Participants who received VV116 within 5 days since the first positive test had a shorter viral shedding time than the control group (8.56 vs 11.13 days), and cox regression analysis showed adjusted HR of 2.37 [95%CI 1.50-3.75], P < 0.001. In symptomatic subgroup, VV116 group had a shorter viral shedding time than the control group ( P = 0.016). A total of 9 adverse events with no serious adverse events were reported in the VV116 group, all of them were resolved without intervention. VV116 is a safe, effective oral antiviral drug, which shows a better performance within the early onset of omicron infection.